Business-Design Laboratory: a Strategy for Innovation (2011)
The contribution of industrial design schools to the development of innovative products is well known around the industrialized world. In Latin American countries like Colombia, industrial design is a relatively young practice and the market is not yet aware of the importance of design as a factor for innovation. Colombia’s industry creativity is just emerging. For many years focus was put on production and contract manufacturing. Today, however, Eastern countries do it on a more larger-scale and at low prices. This condition has forced the academia to look for ways of linking companies with students and thus, developing more competitive innovation products.